Genotypic variation for tolerance to low soil phosphorous in common bean under controlled screen house conditions - Namayanja, Annet; Semoka, Johnson; Buruchara, Robin Arani; Nchimbi, Susan; Waswa, Moses (Scientific Research Publishing, Inc., 2014)
Production of common bean (Phaseolus vulgaris) is often limited by the low availability of soil phosphorus (P). Identification of common bean genotypes adapted to low phosphorus (P) availability may be a feasible strategy to overcome the poor plant growth and production in P-deficient soils. Genetic variation for P response of thirteen common bean genotypes was studied under screen house controlled conditions using triple super phosphate as P source. The common bean genotypes varied in leaf area, shoot mass, root mass, total root length, basal and lateral roots production, shoot P concentration and P uptake under phosphorous deficiency and high phosphorous. All the measured variables were significantly correlated with each other, which in turn were correlated to P uptake. Generally the large-seeded genotypes RWR 1946 and RWR 2075 appeared to have the best growth, hence superior P efficiency under low P availability, while at the same time they were more responsive to added P. These results complement the earlier field based observed tolerance to low soil phosphorous of the selected genotypes under the BILFA strategy.